2003
DOI: 10.1046/j.1471-4159.2003.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Obliteration of α‐melanocyte‐stimulating hormone derived from POMC in pituitary and brains of PC2‐deficient mice

Abstract: Alpha-melanocyte-stimulating hormone (a-MSH) is a neuropeptide expressed in pituitary and brain that is known to regulate energy balance, appetite control, and neuroimmune functions. The biosynthesis of a-MSH requires proteolytic processing of the proopiomelanocortin (POMC) precursor. Therefore, this study investigated the in vivo role of the prohormone convertase 2 (PC2) processing enzyme for production of a-MSH in PC2-deficient mice. Specific detection of a-MSH utilized radioimmunoassay (RIA) that does not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…PC2-null mice weigh 5-18% less than their wild-type counterparts with no gross anatomic disturbances (16). They lack pituitary and brain ␣-MSH and demonstrate high levels of ACTH in the pituitary and hypothalamus (24,32) due to the inability to process ␣-MSH from ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…PC2-null mice weigh 5-18% less than their wild-type counterparts with no gross anatomic disturbances (16). They lack pituitary and brain ␣-MSH and demonstrate high levels of ACTH in the pituitary and hypothalamus (24,32) due to the inability to process ␣-MSH from ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…Among many neuropeptides examined (56-65), α-MSH (derived from POMC) was nearly absent in PC2 deficient mice (56). Results of neuropeptide studies in PC2 null mice revealed three characteristic types of findings.…”
Section: Pc2 and Pc1/3 Deficient Micementioning
confidence: 96%
“…Extensive comparisons of multiple neuropeptides in different tissues of PC2 null mice demonstrated the selective effects of PC2 (56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Among many neuropeptides examined (56-65), α-MSH (derived from POMC) was nearly absent in PC2 deficient mice (56).…”
Section: Pc2 and Pc1/3 Deficient Micementioning
confidence: 99%
“…PC1/3-deficient mice exhibited severe impairment of ACTH production and compensatory accumulation of POMC mRNA in the pituitary (Zhu et al 2002). Using refined immunological techniques with specific antibodies (Miller et al 2003) showed that the pituitary and hypothalamus of PC2-deficient mice lacked α-MSH, accumulating ACTH, ACTH-containing intermediates, and POMC as well as β-endorphin(1-31). The impaired processing was largely confirmed by mass spectrometry-based peptidomics (Wardman & Fricker 2011).…”
Section: The Enzymes Cleave the Prohormone Into Peptides Normally Foumentioning
confidence: 99%